EL PROCESO CREATIVO DE LA INTERFAZ DEL SISTEMA DE GESTIÓN DE LA INFORMACIÓN* - KAFURE, Ivette (BIBLIOPOLIS, 2020)
Often, users get to know the information management system (SGI) while using it. This can cause problems in information retrieval, especially if there is a discrepancy between the needs and expectations of the user and the representation of the task to be accomplished in the interface. This paper illustrates the design of the SGI interface from its inception. It takes into account the user, the task (mental model), and the completion of the task (activity), with the support of cognitive ergonomics, the emotional design, usability, and an evaluation of the interface project. The techniques applied to this end were the analysis of the task and activity, systematic observation, paper prototyping, the target group, the questionnaire, the interview, and card management. The use of these techniques was based on the logic employed by the users and the logic of analysts and information professionals. This can facilitate the development and implementation of suggestions that would add value to the understanding and the analysis of the issues involved in the design of the SGI interface and it can also encourage increased user satisfaction.